Combining ability for foliar diseases, insect-pests and quality in forage sorghum (Sorghum bicolor) - RAJESH YADAV; S K PAHUJA (The Indian Journal of Agricultural Sciences, 2014)
Combining ability analysis was carried out following Line × Tester analysis for green fodder yield, stem girth, ºBrix, important foliar diseases, shoot fly and stem borer in nine male sterile lines, four testers and their thirty six hybrids in forage sorghum [Sorghum bicolor (L.) Moench.]. Highly significant variances for lines as well as testers were observed indicating presence of wide range of genetic variation among the lines and testers for most of the traits. Variance due to Lines × Testers interaction was also found highly significant for all the characters studied except sooty stripe disease. The estimates of sca variances were higher than those of gca for all the characters suggesting predominance of non-additive gene action in all the traits studied. Among the lines ICSA 725 and ICSA 467 were found to be the best combiners whereas among the testers G 203 and SDSL 92113 were found to be superior when yield and resistance to diseases and insect were considered together. Among the hybrids, 95A × SSG 59-3, 296A × SSG 59-3, 467A × SSG 59-3, 467A × SDSL 92113 and 725A × SSG 59-3 were having better sca effects for yield and resistance traits.